Rehabilitation for foot/ankle - Continuous Passive motion (CPM) using Shape Memory Alloy (SMA) actuated Stewart platform - Krishnan, S. (Asian Research Publishing Network, 2016)
The research was mainly focused towards developing a device that was economical and affordable to patients recovering from foot and ankle injuries with a better chance of rehabilitation in comparison to the existing devices. The Mechanical properties of Shape Memory Alloy (SMA) wires which are used as actuators in the Stewart platform rehabilitation device are experimentally investigated to estimate displacement and force developed. In order to investigate the relationship between force and deflection of the upper platform, a accelerometer (ADXL335 with 3 axis) has been mounted on the moving platform to measure the deflection angle. Six force sensors have been fabricated and mounted with a three pairs of strain gauges to measure the force developed by the respective actuators. Calibration of the Sensor has been accomplished with known weights and for the tilt sensor with the indexing table of a CNC (Computerized Numerical Control) machine. SMA wires actuated Stewart platform rehabilitation device had been designed, fabricated and tested experimentally with the transducers mentioned above. The prototype is demonstrated to the orthopedic departments of the hospital and the trails were conducted with the experts for their opinion and feedback. They were enthusiastic and very much in favors for this device. Â© 2006-2016 Asian Research Publishing Network (ARPN).